Sierra Leone : Jobs Diagnostic - Gonzalez, Alvaro S.; Michel Gutierrez, Veronica (World Bank, Washington, DC, 2017)
Sierra Leone is a relatively small economy with potential for jobs-rich growth. It is an extremely poor nation with substantial mineral, agricultural, and fishery resources. Nearly half of the working-age population engages in subsistence agriculture. Alluvial diamond mining remains the major source of hard currency earnings, accounting for nearly half of exports. However, the anticipated job-rich recovery is unlikely to be realized simply from the continued exploitation of the minerals underneath Sierra Leonean soil. This Jobs Diagnostic of Sierra Leone is a first, modest, but necessary, step to formulate that focused effort to create good jobs. It provides a better understanding of the job creation performance of the economy. It identifies the major problems that hold back the economy from creating good, formal-sector jobs that will lift people out of poverty and get them on the road to upward mobility. The Jobs Diagnostic begins with a look at the jobs creation performance of the economy. It then provides an examination of the labor supply—the state of the present and future workers and entrepreneurs. Finally, this diagnostic looks at job performance of firms—the potential employers and job creators.